2014
DOI: 10.35652/igjps.2014.110
|View full text |Cite
|
Sign up to set email alerts
|

Low Birth Weight & Associated Factors Among Newborns in Gondar Town, North West Ethiopia: Institutional Based CrossSectional Study

Abstract: BACKGOUND: Reducing infant mortality is a global priority which is particularly relevant in developing countries including Ethiopia. One of the key strategies to reduce infant mortality rate and improving child health is improving birth weight; however, low birth weight is significantly higher in Ethiopia. The main aim of this study was to determine prevalence and identify associated factors of low birth weight among newborns in Gondar town, North West Ethiopia.METHODS: An institution based cross-sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
6
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 10 publications
7
6
1
Order By: Relevance
“…In an analysis of associated factors, newborns born to women who reside in rural areas had a 2.5 higher risk of having birth asphyxia than those born to women who live in the city. This finding is in line with research was undertaken in Nepal [24], Gondar [25], Dire Dawa [26], and Wollo [27], which found that moms in rural areas had poorer birth outcomes than mothers in urban areas. This could be because the research locations are similar in terms of socioeconomic and lifestyle conditions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In an analysis of associated factors, newborns born to women who reside in rural areas had a 2.5 higher risk of having birth asphyxia than those born to women who live in the city. This finding is in line with research was undertaken in Nepal [24], Gondar [25], Dire Dawa [26], and Wollo [27], which found that moms in rural areas had poorer birth outcomes than mothers in urban areas. This could be because the research locations are similar in terms of socioeconomic and lifestyle conditions.…”
Section: Discussionsupporting
confidence: 91%
“…Despite the fact that prenatal asphyxia contributes significantly to neonatal morbidity and mortality in underdeveloped countries, evidence is scarce on the factors that predict perinatal asphyxia. There isn't enough evidence to say whether maternal or neonatal variables play a role in the occurrence of birth asphyxia [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy induced hypertension was another factor significantly associated with the birth weight in the current finding and that mother who had pregnancy induced hypertension are more likely to deliver low birth weight baby compared to those who had not. This finding is consistent with the study done in Gonder (24) and Addis Ababa (26). This might be due to the reduction in the delivery of nitrogen and oxygen to the placenta as a result of the decrease of the blood flow through spiral artery so the birth weight of the neonates will become lower as a result.…”
Section: Prevalence Of Low Birth Weightsupporting
confidence: 93%
“…2 In developing countries, the cause of LBW is premature birth, whereas intrauterine growth restriction in developed nations. 3 Low birth weight is the most critical risk for neonate mortality, 4 which contributes 60-80% of neonatal morbidity and mortality. 5 LBW newborns are almost 20 times at high risk to die than newborns with normal birth weight.…”
Section: Introductionmentioning
confidence: 99%